Environmental Life Cycle Assessment of Class A Biosolids Production Using Conventional and Low-Cost, Low-Tech Processes at Small Water Resource Recovery Facilities - Janna L. Brown; Robert M. Handler; Jennifer G. Becker; Eric A. Seagren (Applied Sciences)
Producing Class A biosolids that can be distributed or land-applied without restriction is a beneficial way to reuse wastewater treatment solids. For small water resource recovery facilities (WRRFs) in particular, low-cost, low-tech (LCLT) processes may be an appealing alternative to conventional technologies for producing Class A biosolids, such as processes to further reduce pathogens (PFRPs). Conventional Class A biosolids treatment processes tend to be energy-intensive and involve complex equipment and operations. However, a systematic comparison of the overall sustainability of conventional processes and LCLT alternatives for producing Class A biosolids to aid decision makers in selecting treatment processes is not readily available. Therefore, this study used life cycle assessments to compare five Class A biosolids treatment processes, including three conventional processes—Composting, Direct Heat Drying, and temperature-phased anaerobic digestion (TPAD)—and two LCLT processes—Air Drying, and long-term Lagoon Storage followed by Air Drying—on the basis of their environmental impacts. The environmental impacts were normalized to facilitate a comparison of the processes. The results indicate that Composting and Direct Heat Drying had the most significant environmental impacts, primarily from the biogenic emissions during Composting and the natural gas requirements for Direct Heat Drying. In comparison, TPAD and Air Drying had the lowest environmental impacts, and Lagoon Storage had intermediate impacts. Thus, LCLT processes may be more sustainable than some, but not all, conventional PFRPs.